THE COMPOSITION GOMBANG FISHING GEAR OF THE OPERATED AT THE EDGE AND MIDDLE AIR HITAM STRAIT BY FISHARMEN VILLAGE SIALANG PASUNG SUB DISTRICT WEST RANGSANG MERANTI ISLAND OF PROVINCE RIAU - Mai Yunizariani; Arthur Brown; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbatractThisresearchwasconductedonJanuary 2018inthe Village Sialang Pasung District west Rangsang Meranti Island Of Province Riu. The purpose of this study was to determine the composition of the gombang fishing gear which is operated on the edge and middle area of the air hitam strait by fishermen in Sialang Pasung Village, Meranti Islands, Riau Province. The gombang fishing gear used in gombang was operated on the edge area by fishermen in Sialang Pasung Village has a total length of 22 m and in the middle of 26.89 m. The catches of gombang was taken in one day / trip and it can be carried out 4 times, that is when 2 tides occuron day and night by using a rowboat. The catch composition of the gombang which is operated at the edge and middle of the water according to the weight (g) and the species it is bilis fish and the lowest catch is the sebelah fish. While the number of catches based on weight (g) and species is 82,178 (g) and the number of catches according to the species is 325,960.            Keywords:Gombang fishing gear operated at the edge and middle